Ultraviolet laser‐induced cross‐linking in peptides. (11th June 2013) - Leo, Gabriella; Altucci, Carlo; Bourgoin‐Voillard, Sandrine; Gravagnuolo, Alfredo M.; Esposito, Rosario; Marino, Gennaro; Costello, Catherine E.; Velotta, Raffaele; Birolo, Leila
Abstract : RATIONALE: The aim of this study was to demonstrate, and to characterize by high‐resolution mass spectrometry that it is possible to preferentially induce covalent cross‐links in peptides by using high‐energy femtosecond ultraviolet (UV) laser pulses. The cross‐link is readily formed only when aromatic amino acids are present in the peptide sequence. METHODS: Three peptides, xenopsin, angiotensin I, and interleukin, individually or in combination, were exposed to high‐energy femtosecond UV laser pulses, either alone or in the presence of spin trapping molecules, the reaction products being characterized by high resolution mass spectrometry. RESULTS: High‐resolution mass spectrometry and spin trapping strategies showed that cross‐linking occurs readily, proceeds via a radical mechanism, and is the highly dominant reaction, proceeding without causing significant photo‐damage in the investigated range of experimental parameters. CONCLUSIONS: High‐energy femtosecond UV laser pulses can be used to induce covalent cross‐links between aromatic amino acids in peptides, overcoming photo‐oxidation processes, that predominate as the mean laser pulse intensity approaches illumination conditions achievable with conventional UV light sources. Copyright © 2013 John Wiley & Sons, Ltd.